Montessori Education at a Distance, Part 2: A Mixed Methods Examination of Montessori Educators’ Response to a Global Pandemic - Murray, Angela K.; Brown, Katie; Barton, Patricia (Journal of Montessori Research, 2021)
This study offers a contextualized understanding of the distance-learning experiences of Montessori educators and students in the spring of 2020 in the wake of the COVID-19 global pandemic. In this article, we build on results reported in a separate article published in this issue of the Journal of Montessori Research. First, we analyzed qualitative data from social media and national virtual gatherings designed to support teachers as they faced the challenges created by the abrupt shift to distance learning. Second, we employed a convergent mixed-methods design to integrate these qualitative findings with the survey results reported in the previous article to provide a richer and more complete perspective on the situation. In our results, we found substantial evidence to support the resilience and durability of the Montessori Method, even in the face of adverse conditions created by a global pandemic. Despite the challenges of adaptation, Montessori educators demonstrated a commitment to the key tenets of Montessori philosophy, such as following the child and employing a holistic perspective on learning and development. While serving the whole child’s growth and development remained front and center, Montessori teachers’ approach to academics looked very different under distance learning. Still, the ongoing attention to children’s social-emotional needs will benefit both teachers and children when they return to the classroom, undoubtedly with lasting effects from pandemic-related isolation and hardship.